Characterization of mechanical, thermal, and morphological properties for long hemp fiber-reinforced green epoxy biocomposites - Siddiqui, Vasi Uddin; Lahmdi, Fahd Salah Hasan; Sapuan, S. M.; Azka, Muhammad Adlan; Khan, Abir; Yusuf, J.; Hasan, Mohammad Zaid; Habib, Abdul (John Wiley and Sons, 2025)
Growing environmental concerns have heightened the demand for eco-friendly materials, prompting a shift from carbon fibers and conventional polymers to recyclable biopolymer composites. Natural fibers, such as hemp, are widely incorporated into green epoxy composites to enhance performance, with applications spanning industries including transportation, aerospace, construction, energy, and shipping. The thermal and mechanical properties of hemp fiber-reinforced green epoxy composites are essential in determining their effectiveness and broader viability. However, challenges such as limited fracture resistance, fragility, low impact strength, and fatigue resistance currently restrict their durability, particularly in demanding applications like automotive engineering. This study investigates the mechanical, thermal, fire, and morphological properties of hemp fiber-reinforced green epoxy composites through comprehensive mechanical, thermal, and flammability testing, as well as SEM analysis to examine fiber behavior and microstructure. The use of green epoxy is also an area that was not deeply explored by the researchers. Furthermore, hemp fibers are known for their tensile strength and environmental benefits, which result in sustainable material production. Results demonstrated significant improvements in flexural strength, with values increasing from 53.654 MPa in neat epoxy to a minimum of 139.834 MPa in reinforced samples. Impact strength also improved, ranging from 4.04 to 8.26 kJ/m2, along with enhanced flame resistance. In conclusion, hemp fiber-reinforced green epoxy composites showed overall performance improvements, except in tensile strength, compared to neat green epoxy samples, underscoring their potential in sustainable material applications. Highlights: Hemp fiber improves green epoxy's flexural and impact strength. Enhanced flame resistance in green epoxy composites with hemp fiber. SEM analysis reveals improved fiber microstructure in composites. The flexural strength of composites exceeds neat green epoxy by 160%.